Designing The Estimation of The Need for Spare Parts and Inventory Policy on The D32 CP8 Compressor Machine - Prasetyo Nugroho, Herlambang; Tatas Dwi Atmaji, Fransiskus; Nopendri, Nopendri (Infotekmesin, 2023)
Based on damage data owned by PT XYZ, the compressor engine that has a history of high damage is the D32 CP8 Compressor Engine. Critical components of the D32 CP 8 Compressor are determined using a risk matrix. The critical components selected from the D32 CP8 Compressor Engine are Screw Motor, Refrigerant Air Cooler, and Cylinder Bearing Oil Cooler. This study uses the Reliability Centered Spares (RCS), Min-Max Stock, and Reorder Point (ROP) methods. The data collection and processing results obtained the need for critical components in the next 1 year based on the MTTF critical component data. These calculations show that the value of the required spare parts for the Motor Screw, Refrigerant Air Conditioner, and Cylinder Bearing Oil Cooler in a year is 8 components. The minimum Stock of the Screw Motor is 3 components, the maximum stock is 8 components, ReOrder Point point is 4 components. The minimum stock of 4 component air coolers, maximum stock of 7 components, ReOrder Point when 3 components. The minimum stock of a Cylindrical Bearing Oil Cooler is 2 components, the maximum stock is 6 components, and the ReOrder Point is when there are 2 components.